Sex-steroids and hypolipidemic chemicals impacts on brown trout lipid and peroxisome signaling — Molecular, biochemical and morphological insights - Madureira, Tânia Vieira (2019)
Lipid metabolism involves complex pathways, which are regulated in a similar way across vertebrates. Hormonal and hypolipidemic deregulations cause lipid imbalance from fish to humans, but the underlying mechanisms are far from understood. This study explores the potential of using juvenile brown trout to evaluate the in vivo interferences caused by estrogenic (17α-ethinylestradiol - EE2), androgenic (testosterone - T), and hypolipidemic (clofibrate - CLF) compounds in lipidic and/or peroxisomal pathways. Studied endpoints were from blood/plasma biochemistry, plasma fatty acid profile, ultrastructure of hepatocytes and abundance of their peroxisomes to mRNA expression in the liver. Both T and CLF caused minimal effects when compared to EE2. Estrogenized fish had significantly higher hepatosomatic indexes, increased triglycerides and very-low density lipoproteins (VLDL) in plasma, compared with solvent control. Morphologically, EE2 fish showed increased lipid droplets in hepatocytes, and EE2 and T reduced volume density of peroxisomes in relation to the hepatic parenchyma. Polyunsaturated fatty acids (PUFA) in plasma, namely n-3 PUFA, increased with EE2. EE2 animals had increased mRNA levels of vitellogenin A (VtgA), estrogen receptor alpha (ERα), peroxisome proliferator-activated receptor alpha (PPARα), PPARαBa and acyl-CoA long chain synthetase 1 (Acsl1), while ERβ-1, acyl-CoA oxidase 1-3I (Acox1-3I), Acox3, PPARγ, catalase (Cat), urate oxidase (Uox), fatty acid binding protein 1 (Fabp1) and apolipoprotein AI (ApoAI) were down-regulated. In summary, in vivo EE2 exposure altered lipid metabolism and peroxisome dynamics in brown trout, namely by changing the mRNA levels of several genes. Our model can be used to study possible organism-level impacts, viz. in gonadogenesis.